(untitled) (Damascus University Journal of agriculture sciences, 2021)
This work Studies the variation of viscosity of pure glycerine and glycerine mixed with water in different proportions as a function of temperature. It also presents best methods to detect glycerine mixed with water and determine the percentage ratio of water in it. This work shows that viscosity of pure glycerine at zero degree centigrade equals 12070 cpoise and it drops gradually to 14.80 c poise at 100 C°. It shows also that pure glycerin has a viscosity equals 1410 c poise at 100 C° and drops to 3900 c poise at 10 C°. It also indicates the importance of lowering the temperature of glycerin for detecting the percentage of water in non-pure glycerin. The importance of this work economically since glycerine is an essential component in antigels used in internal combustion engines and if it is mixed with water this will lead to cracks in parts of the engine.